The Mississippi hustle: corrupting the financial principal-agency relationship at the Mississippi Department of Corrections - McElreath, David H. (Crime, law and social change, 2017)
The financial management of justice system organizations necessitates the invoking and exercising of a fiduciary principal-agency relationship between corrections administrators and their respective stakeholders. In the context of correctional operations, this means the principal (the state and, by extension, the citizens) entrusts agency personnel (administrators) to carry out their duties in an ethical fashion to provide maximum benefit to the principals. Although it is expected that justice system administrators are above reproach, such an expectation is not always realistic. This paper examines the Mississippi Hustle criminal investigation that targeted financial corruption in the Mississippi Department of Corrections. The Mississippi Hustle incident represented an egregious violation of the financial principal-agency relationship with respect to financial fraud and contract scandal. As a result of the investigation, the former corrections commissioner and a former legislator each face decades as inmates within the prison system.